Examining Job Description to Develop Job Performance Indicators for Higher Education Institution Based on MBNQA Education Criteria - Sondari, Mery Citra (Journal of Education and Vocational Research, 2013)
Higher Education Institution quality has important impact to national development, in this knowledge-based economy ages. However Higher Education Institutions (HEI) in Indonesia is far lag behind, compare to some of contries in the region of South East Asia.Therefore, HEI in Indonesia should benchmark to World Class Performance Frameworks, one of them is MBNQA. This paper aims to develop job performance indicators as guidance for HEI administrator to be able to achieve the MBNQA criteria. This paper linking organizational performance measurement indicators based on MBNQA, with individual job’s performance indicator. From case study at Faculty of Economics and Bussiness Universitas Padjadjaran, Indonesia, by using descriptive content analysis of actual job description, this research find that the MBNQA indicators are not fully covered in actual job description. Further research is still needed to validate the proposed job performance indicators.